Durable response of breast cancer leptomeningeal metastasis to capecitabine monotherapy - Rogers, Lisa R. (Duke University Press, 2004)
We report a durable (12-month) response to capecitabine monotherapy, shown clinically, by MRI, and by cerebrospinal fluid analysis, in a patient with leptomeningeal metastasis from breast cancer.